A community-based peer support service for persons with severe mental illness in China - Yunge Fan; Ning Ma; Liang Ma; Wei Xu; J. Steven Lamberti; Eric D. Caine (BMC Psychiatry, 2018)
Abstract Background Peer support services for patients with severe mental illness (SMI) originated from Western countries and have become increasingly popular during the past twenty years. The aim of this paper is to describe a peer service model and its implementation in China, including the model’s feasibility and sustainability. Methods A peer support service was developed in four Chinese communities. Implementation, feasibility and sustainability were assessed across five domains: Service process, service contents, peer training and supervision, service satisfaction, and service perceived benefit. Results Service process: 214 peer support activities were held between July 2013 and June 2016. No adverse events occurred during three years. Each activity ranged from 40 to 120 min; most were conducted in a community rehabilitation center or community health care center. Service content: Activities focused on eight primary topics—daily life skills, social skills, knowledge of mental disorders, entertainment, fine motor skill practice, personal perceptions, healthy life style support, emotional support. Peer training and supervision: Intensive training was provided for all peers before they started to provide services. Regular supervision and continued training were provided thereafter; online supervision supplemented face to face meetings. Service satisfaction: Nineteen consumers (79.2%) (χ2(1) = 12.76, p < 0.001) were satisfied with the peers and 17 consumers (70.8%) (χ2(1) = 8.05, p = 0.005) expressed a strong desire to continue to participate in the service. Fourteen caregivers (93.3%) (χ2(1) = 11.27, p = 0.001) wanted the patients to continue to organize or participate in the service. Service perceived benefit: Six peers (85.7%) (χ2(1) = 3.57, p = 0.059) reported an improvement of working skills. Ten consumers (41.7%) (χ2(1) = 0.05, p = 0.827) reported better social communication skills. Six caregivers (40%) (χ2(1) = 1.67, p = 0.197) observed patients’ increase in social communication skills, five (33.3%) (χ2(1) = 1.67, p = 0.197) found their own mood had been improved. Conclusions Peer support services for patients with SMI can be sustainably implemented within Chinese communities without adverse events that jeopardize safety and patient stability. Suggestions for future service development include having professionals give increased levels of support to peers at the beginning of a new program. A culturally consistent peer service manual, including peer role definition, peer training curriculum, and supervision methods, should be developed to help implement the service smoothly.